Growth hormone prescribing patterns in the UK, 2013–2016. Issue 6 (19th December 2018) - Shepherd, Sheila; Saraff, Vrinda; Shaw, Nick; Banerjee, Indraneel; Patel, Leena
Abstract : Introduction: Prescribing of recombinant human growth hormone (rhGH) for growth failure in UK children is based on guidance from the National Institute for Health and Care Excellence. In 2013, the British Society for Paediatric Endocrinology and Diabetes initiated a national audit of newly prescribed rhGH treatment for children and adolescents. In this review, we have examined prescribing practices between 2013 and 2016. Methods: All patients ≤16.0 years of age starting rhGH for licensed and unlicensed conditions in the UK were included. Anonymised data on indication and patient demographics were analysed. Results: During the 4 years, 3757 patients from 76 of 85 (89%) centres started rhGH. For each licensed indication, proportions remained stable over this period: 56% growth hormone deficiency (GHD), 17% small for gestational age (SGA), 10% Turner syndrome, 6% Prader-Willi syndrome (PWS), 3% chronic renal insufficiency (CRI) and 2% short stature homeobox deficiency (SHOXd). However, the unlicensed category decreased from 10% (n=94) in 2013 to 5% (n=50) in 2016. The median age of patients starting rhGH was 7.6 years (range 0.1–16.0). Patients with PWS were significantly younger (median 2.2 years, range 0.2–15.1) compared with other indications (p<0.0001) and were followed by the SGA group (median 6.2 years, range 1.3–15.6, p<0.0001). Boys predominated in all groups except for PWS and SHOXd. Conclusion: We demonstrate significant engagement of prescribing centres in this audit and a decline in unlicensed prescribing by half in this 4-year period. Patients in the PWS group were younger at initiation of rhGH compared with other indications and had no male predominance unlike GHD, SGA and CRI.